The impact of mistakes at the micro level of pronunciation on the assessment of English Phonetics and Phonology II students' oral performance” - Canavosio, Andrea (2015)
This study aims at determining the impact of mistakes at the micro level or pronunciation on the assessment of undergraduate EFL (English as a foreign language) students in the context of the subject Phonetics and Phonology II at the School of Languages, National University of Córdoba. More precisely, the study aims at a) identifying the micro level mistakes, both segmental and supra segmental, that students produce during Phonetics and Phonology II final oral exams and b) determining the impact of these mistakes on their performance assessment. To meet the objectives, the samples were collected during final oral exams and the marks students got were registered; then the samples were analysed so as to identify the micro level mistakes; the mistakes were classified following Morley‟s (1994) taxonomy; last, statistical tests were run in order to determine the impact of mistakes on the final mark assigned to participants. This thesis is divided into four chapters. Chapter I describes the state of research and presents the theoretical framework. It is divided into three different sections. Section 1 presents several studies that deal with different aspects of pronunciation assessment in a variety of contexts. In Section 2, the concept of language proficiency is traced back to its origins and then the concept of Communicative Language Ability, put forward by Bachman (1990) and Bachman and Palmer (1996, 2010), is analysed. Finally, Morley‟s (1994) Dual Focus Approach to the teaching of pronunciation is described. In section 3, language assessment is defined, different testing methods are revised and the Phonetics and Phonology II final oral exam is described. Furthermore, pronunciation assessment in particular is discussed, together with the concept of error and the functional load principle. Reference is made to the tendency of focusing either on segmental or supra segmental features during pronunciation assessment. Chapter II consists of two sections. In the first one, the context of this research study is described. Reference is made to the role of pronunciation in the programmes of study of the School of Languages, to its students and 5 teachers, and to the course Phonetics and Phonology II. In the second section, the study is presented: the research questions, objectives, methodology and procedures are thoroughly detailed. In Chapter III, results are presented and discussed. First, a descriptive statistical analysis is made to the data to examine the occurrence of micro level mistakes and the marks students were given. Then, the results of linear regression and multiple regression tests are presented to determine the impact of micro level mistakes on students‟ final marks. Chapter IV presents the conclusions reached in the study. There are also a number of suggestions for further research for people who are interested in doing research in the area of pronunciation assessment. It is expected that this work should constitute a contribution to the field of pronunciation assessment in educational contexts where English pronunciation is taught to prospective EFL professionals.